2019
DOI: 10.1109/access.2019.2923809
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-Acoustic Methods in the Condition Assessment of Power Transformers: A Survey

Abstract: It has been over two decades since the publication of pioneer works about the power transformer diagnostics based on monitoring of their acoustic fingerprints. Since then, there has been great progress in this field and the methods used are as complex as ever. Any unnecessary intervention on a power transformer implies its temporary disconnection from the power grid. The inability to supply electricity to the customer means not only financial loss for the utility but also generates a non-material loss, e.g., t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 78 publications
(97 reference statements)
1
35
0
Order By: Relevance
“…In the FE model, the hysteresis phenomenon is ignored, and the mean value is used instead. The electromagnetic force distribution can be obtained by establishing a 2-D axisymmetric model in ANSYS [9]. The axial electromagnetic force amplitude defined in (2) is obtained when the input current is 75 A, which is shown in Fig.…”
Section: Finite-element Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FE model, the hysteresis phenomenon is ignored, and the mean value is used instead. The electromagnetic force distribution can be obtained by establishing a 2-D axisymmetric model in ANSYS [9]. The axial electromagnetic force amplitude defined in (2) is obtained when the input current is 75 A, which is shown in Fig.…”
Section: Finite-element Simulationmentioning
confidence: 99%
“…Increased concerns about fault detection and diagnosis efficiency in a smart-grid context have motivated research into developing online non-intrusive monitoring techniques [5]. Previous studies have shown that transformer vibration is connected with the mechanical properties of windings, and the vibration technique has been used to provide diagnostic information [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The SPL can be expressed as (4), where Prms is the rootmean-square (RMS) value of the sound pressure and Pref Thus, it is important to investigate the relationship between the sound pressure and Lorentz force generated by the windings to predict the load noise of a 3-phase transformer.…”
Section: A Expression Of Splmentioning
confidence: 99%
“…There are several kinds of transformer noise; load noise, caused by the electromagnetic force generated by the interaction between electric and magnetic fields; core noise, produced by magnetostriction of the laminated core; cooling noise, generated by the cooling components of transformers such as cooling fans. Among these noise sources, load noise becomes the dominant source of total transformer noise with an increase in the transformer power [2]- [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation